PRINSIP VICARIOUS LIABILITY DALAM PENYELESAIAN PERKARA PIDANA ANAK - Astri Astari (2022)
Children as human beings who are immature in committing crimes often only fulfill the actus reaus element, and do not have mens rea. Children's actions are still very easily influenced by their surroundings, so there is a responsibility of parents towards their children. For this responsibility, parents can be held accountable. This responsibility can occur if there are 3 points, namely the parent's greater fault, the existence of specific knowledge, and the parent's error. This legal research uses secondary qualitative data which can come from primary legal sources or secondary legal sources. This legal research is not limited to legal disciplines, but still elaborates it with understanding and other knowledge that is relevant to the study used. In the context of the ius constituendum, vicarious liability can occur because it is contained in Article 37 letter b of the RKUHP and then further regulation is needed in the Child Protection Act. The concept can follow the diversion qualification with an additional 3 points in parental responsibility.